The challenges of higher education in the context of globalization - Solano Alpízar, José (2011)
This paper makes a characterization of some of the challenges facing higher education in the face of accelerating changethat globalization has brought, and suggests possiblecourses of action that contribute to education superior suits the context without losing its commitment to socio-cultural Costa Rican society.For expository purposes the paper is structuredthree parts: the first is a brief characterization of the phenomenon of globalization, the second one required some of the challenges thatfacing higher education as a result of thechanges in their environment, both nationally andinternationally, and in the third part outlines some challenges that require ongoing reflection process on the part of people who arecommitted to education superior.